Novel tunable filter for millimeter-wave spectrum analyzer over 100 GHz - Kawamura, Takashi; Shimotahira, Hiroshi; Otani, Akihito (2013 IEEE International Instrumentation and Measurement Technology Conference (I2MTC), 2013)
Rapid progress in millimeter-wave wireless communication technologies requires accurate spectrum analysis in the frequency domain over 100 GHz. A tunable preselection filter is a key device in building such a spectrum analyzer. This paper proposes a new tunable filter as a preselector in the frequency range from 110 to 140 GHz. The filter was designed using a commercial electromagnetic simulator and a prototype was evaluated. Filter measurements were in qualitative agreement with simulator predictions and subjects for practical use are clarified.